Industrialização e imprensa : o debate acerca da indústria automobilística durante o governo JK (1956-1961) - Ganster, Rafael (2017)
The present work seeks to analyze the insertion of the great Rio press in the debate about the process of installation of the automobile industry during the government of Juscelino Kubitschek (1956-1961). The proposed clipping delimits the research in three newspapers of great circulation and prestige in the Carioca society of the period, they are: Última Hora; Jornal do Brasil; O Globo. The choice of these journals takes into account the different positions that, according to historiography, have been presented by them in relation to themes relevant to Brazilian society. It is worth mentioning that this aspect has sometimes been the object of a linear reading of researchers who have studied the subject, crystallizing over the years by the repetition of the arguments, but which, according to what we seek to present, does not hold up after a more detailed empirical research. In addition to a simple framing of position in relation to ideological currents (neoliberal, developmentalist, socialist), we seek to present arguments that support the hypothesis that, avoiding reductionism, the position of the great newspapers must be understood within a broader universe and, fundamental condition, in relation to the other vehicles involved in the dispute for the imposition of a (more) legitimate view on the subject. The analysis of the arguments presented by the press in relation to the automobile industry is fundamental to the objectives we are proposing, since it was at the center of heated debates (political and economic) and constituted as a "revitalizing sector" of the project proposed by Juscelino from the Plano de Metas (Plan of Goals). Moreover, it allows access to essential topics for reading the positions taken, such as state intervention, economic planning, foreign capital regulation, customs protection, exchange control, role of development banks, administrative apparatus, among others.